Low-frequency vibrations of polyamide-6 as a function of temperature and thermal history investigated by terahertz absorption spectroscopy. (June 2015) - Suzuki, Hal; Ishii, Shinya; Otani, Chiko; Hoshina, Hiromichi
Graphical abstract: Highlights: THz spectra of polyamide-6 were obtained for liquid and crystalline α and γ phases. The bands at 6.5 and 8.7 THz for the α crystal were assigned to be lattice modes. These modes were found to be coupled with glass transition in the amorphous phase. A significant annealing effect was found in the THz spectra. Abstract: The α and γ crystals of polyamide-6 were examined by terahertz absorption spectroscopy from −90 to 230 °C. For the α crystals, the absorption band at 6.5 THz, assigned as a lattice vibration perpendicular to the molecular chain, decreased in intensity with increasing temperature, ending near the Brill transition temperature ( T Brill ≈ 160 °C). The band at 8.7 THz, assigned as the skeletal vibration along the molecular chain, shifted to higher frequency with increasing temperature. The rate of shift changed at the glass transition temperature ( T g ≈ 50 °C), indicating coupling of the molecular vibration in the crystal with freezing/relaxing phenomena in the surrounding amorphous phase. A significant annealing effect was observed. On heating polyamide-6 films that had been annealed at a temperature ( T ann ) ⩾80 °C, an increase in spectral intensity above 9 THz occurred at ∼ T ann, due to the melting of semi-crystals formed by recrystallization during annealing.